INTERNATIONAL EXPERIENCES IN DEVELOPING LINGUISTIC COMPETENCE OF HIGH SCHOOL STUDENTS IN ENGLISH CLASSES - Ergasheva Rano (Modern American Journals, 2025)
The globalized nature of modern society necessitates the acquisition of English language skills for effective communication and participation in international discourse. High school education serves as a critical foundation in this process, particularly through English language instruction. This article explores various international experiences and approaches in developing linguistic competence among high school students in English classes. Drawing on examples from countries such as Finland, Japan, Germany, Uzbekistan, India, and the United States, the article examines pedagogical strategies, cultural integration, assessment methodologies, teacher training, and the use of digital tools. These global insights aim to inform educators and policymakers about successful practices that foster both functional and academic language proficiency in adolescents.
Keywords: Linguistic competence, high school education, English as a foreign language, international experiences, language pedagogy, ESL/EFL instruction, global education.